Regulatory Emotional Self-Efficacy and Social Self-Efficacy: Validation evidence of related constructs - Iaochite, Roberto Tadeu [UNESP]; Noronha, Ana Paula Porto; Casanova, Daniela Couto Guerreiro; dos Santos, Acácia Aparecida Angeli; Azzi, Roberta Gurgel (FapUNIFESP (SciELO), 2022)
This study aimed to seek evidence of validity for the Self-Efficacy Scale for Emotional Regulation (SESER) using the relationship with the Emotional Self-Regulation Scale (ESRE) and the Social Self-Efficacy Scale (SSES). Participants included a total of 549 students aged between 13 and 23 years old (M = 16.82, SD = 1.551) from the Brazilian municipalities of Belém (72.7%, n = 399) and Rio de Janeiro (27.3%, n = 150). They responded to SEERS and two other instruments, one that assessed emotional self-regulation in the face of sadness (Emotional Self-Regulation Scale - ESRS) and another that assessed social self-efficacy (Social Self-Efficacy Scale - SSE). The results indicated that emotional self-regulation showed higher rates of prediction for emotion regulation self-efficacy than for social self-efficacy, although both constructs generated significant coefficients. The findings corroborate the literature, confirming the evidence of validity for the Self-efficacy Scale for Emotional Regulation and are discussed in the light of theoretical assumptions.
Autoeficacia para la regulación emocional y autoeficacia social: Búsqueda de evidencias de validez de los constructos relacionados
Autoeficácia para Regulação Emocional e Autoeficácia Social: Busca de Evidências de Validade de Construtos Relacionados
Keywords: Adolescence; Emotional regulation; Psychological assessment; Social cognitive theory